THE ROLE OF DIGITAL MARKETING IN IMPROVING CUSTOMER PERCEIVED VALUE: AN APPLIED STUDY ON IRAQI AIRWAYS CUSTOMERS - Lect. Adnan Rashid A wad (Scholars Digest Publishing, 2025)
This study was conducted by outlining an intellectual and conceptual framework comprising two main variables: the independent variable, digital marketing, and the dependent variable, the customer’s perceived value. Each variable encompassed several dimensions. Digital marketing involved (attraction, immersion, retention, learning, communication), while the customer’s perceived value involved (social value, economic value, functional value, emotional value). Given the modern nature of digital marketing and its necessity in digitally-oriented organizations, Iraqi Airways was selected as the study’s field. The researcher used a questionnaire as the tool to collect essential data for the study, applying the comprehensive survey method to gather opinions from the study population of (130), of which (122) questionnaires were valid for analysis and were examined using the statistical program (SPSS), relying on various statistical tools (arithmetic mean, weighted arithmetic mean, response intensity, standard deviation, etc.). The purpose of this study was to determine the relationship between digital marketing and the customer’s perceived value and the degree to which digital marketing enhances the customer’s perceived value.
Keywords: Digital Marketing, Perceived Customer Value, Iraqi Airways.